Practical Readiness of Graduates: Phenomenology of Basic Media Mastery in KPI Semester 5 Students - Muhammad Gani Ray; Kahpi, Muhammad Latip; Dianto , Icol (Islamic Journal of Communication and Public Discourse, 2026)
Background: This study examines the practical readiness of fifth-semester students in the Islamic Broadcasting Communication (KPI) Study Program to master basic media skills amid increasing demands for practice-oriented media education.Objective: The objective of the study is to explore how students perceive and demonstrate their readiness for media production practices.Method: A phenomenological approach was employed to capture the meaning of participants' lived experiences, using data triangulation through self-report surveys, video analysis of documentation and assignment products, and in-depth interviews with 16 participants.Findings and Implications: The findings indicate an early-stage readiness, characterized by strong digital habits and high self-confidence, while verified production skills remain limited. Video observations reveal weaknesses in pre-production planning, visual narrative continuity, and fundamental technical aspects such as framing and audio quality. Phenomenological interviews further show that students' understanding of media ethics tends to be normative and is not yet critically reflected in production practices. The triangulated results highlight a gap between perceived readiness and observable practical competence, indicating the need for pedagogical intervention.Conclusion: This study concludes that strengthening pre-production instruction, implementing portfolio-based assessments with technical rubrics, and integrating reflective ethical tasks are essential to enhance the verifiability of practical competence and graduates' readiness as media practitioners.